Potent STING activation stimulates immunogenic cell death to enhance antitumor immunity in neuroblastoma - Marjan Rafat; Justin M. Balko; Lihong Wang-Bishop; Mohamed Wehbe; Daniel Shae; Jamaal James; Benjamin C. Hacker; Kyle Garland; Plamen P. Chistov; John T. Wilson (Journal for ImmunoTherapy of Cancer)
Background Neuroblastoma (NB) is a childhood cancer for which new treatment options are needed. The success of immune checkpoint blockade in the treatment of adult solid tumors has prompted the exploration of immunotherapy in NB; however, clinical evidence indicates that the vast majority of NB patients do not respond to single-agent checkpoint inhibitors. This motivates a need for therapeutic strategies to increase NB tumor immunogenicity. The goal of this study was to evaluate a new immunotherapeutic strategy for NB based on potent activation of the stimulator of interferon genes (STING) pathway.Methods To promote STING activation in NB cells and tumors, we utilized STING-activating nanoparticles (STING-NPs) that are designed to mediate efficient cytosolic delivery of the endogenous STING ligand, 2’3’-cGAMP. We investigated tumor-intrinsic responses to STING activation in both MYCN-amplified and non-amplified NB cell lines, evaluating effects on STING signaling, apoptosis, and the induction of immunogenic cell death. The effects of intratumoral administration of STING-NPs on CD8+ T cell infiltration, tumor growth, and response to response to PD-L1 checkpoint blockade were evaluated in syngeneic models of MYCN-amplified and non-amplified NB.Results The efficient cytosolic delivery of 2’3’-cGAMP enabled by STING-NPs triggered tumor-intrinsic STING signaling effects in both MYCN-amplified and non-amplified NB cell lines, resulting in increased expression of interferon-stimulated genes and pro-inflammatory cytokines as well as NB cell death at concentrations 2000-fold to 10000-fold lower than free 2’3’-cGAMP. STING-mediated cell death in NB was associated with release or expression of several danger associated molecular patterns that are hallmarks of immunogenic cell death, which was further validated via cell-based vaccination and tumor challenge studies. Intratumoral administration of STING-NPs enhanced STING activation relative to free 2’3’-cGAMP in NB tumor models, converting poorly immunogenic tumors into tumoricidal and T cell-inflamed microenvironments and resulting in inhibition of tumor growth, increased survival, and induction of immunological memory that protected against tumor re-challenge. In a model of MYCN-amplified NB, STING-NPs generated an abscopal response that inhibited distal tumor growth and improved response to PD-L1 immune checkpoint blockade.Conclusions We have demonstrated that activation of the STING pathway, here enabled by a nanomedicine approach, stimulates immunogenic cell death and remodels the tumor immune microenvironment to inhibit NB tumor growth and improve responses to immune checkpoint blockade, providing a multifaceted immunotherapeutic approach with potential to enhance immunotherapy outcomes in NB.